PVALB, a New Hurthle Adenoma Diagnostic Marker Identified through Gene Expression - Cerutti, Janete Maria [UNIFESP] (2011)
Context: A better means to accurately identify malignant thyroid nodules and to distinguish them from benign tumors is needed. We previously identified markers for detecting thyroid malignancy, with sensitivity estimated at or close to 100%. One lingering problem with these markers was that false positives occurred with Hurthle cell adenomas (HCA) which lowered test specificity.Methods: To locate accurate diagnostic markers, we profiled in depth the transcripts of a HCA and a Hurthle cell carcinoma (HCC). From 1146 differentially expressed genes, 18 transcripts specifically expressed in HCA were tested by quantitative PCR in a wide range of thyroid tumors (n = 76). Sensibility and specificity were calculated using receiver operating characteristic (ROC). Selected markers were further validated in an independent set of thyroid tumors (n = 82) by immunohistochemistry. To define the panel that would yield best diagnostic accuracy, these markers were tested in combination with our previous identified markers.Results: Seventeen of the 18 genes showed statistical significance based on a mean relative level of expression (P < 0.05). KLK1 (sensitivity = 0.97) and PVALB (sensitivity = 0.94) were the best candidate markers. the combination of PVALB and C1orf24 increased specificity to > 97% and maintained sensitivity for detection of carcinoma.Conclusion: We identified tumor markers that can be used in combination for a more accurate preoperative diagnosis of thyroid nodules and for postoperative diagnosis of thyroid carcinoma in tumor sections. This improved test would help physicians rapidly focus treatment on true malignancies and avoid unnecessary treatment of benign tumors, simultaneously improving medical care and reducing costs. (J Clin Endocrinol Metab 96: E151-E160, 2011)